Milk fat components with potential anticancer activity—a review - Luís M. Rodriguez‐Alcalá; María Pilar Castro-Gómez; Lígia L. Pimentel; Javier Fontecha (2017)
During many years, the milk fat has been unfairly undervalued due to its association with higher levels of cardiovascular diseases, dyslipidaemia or obesity, among others. However, currently, this relationship is being re-evaluated because some of the dairy lipid components have been attributed potential health benefits. Due to this, and based on the increasing incidence of cancer in our society, this review work aims to discuss the state of the art concerning scientific evidence of milk lipid components and reported anticancer properties. Results from the in vitro and in vivo experiments suggest that specific fatty acids (FA) (as butyric acid and conjugated linoleic acid (CLA), among others), phospholipids and sphingolipids from milk globule membrane are potential anticarcinogenic agents. However, their mechanism of action remains still unclear due to limited and inconsistent findings in human studies.